2018
DOI: 10.1007/s10903-018-0821-7
|View full text |Cite
|
Sign up to set email alerts
|

Working Below Skill Level as Risk Factor for Distress Among Latin American Migrants Living in Germany: A Cross-Sectional Study

Abstract: About 84,710 Latin American migrants currently live in Germany. Knowledge about their work situation in relation to their skill level and its association with mental health is limited. Therefore, the aims of this study were to assess the prevalence of working below skill level and its association with the prevalence of distress in Latin Americans living in Germany. This cross-sectional study included a convenience sample of 282 Latin American migrants living in Germany. Participants were recruited by a short o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The 12-months prevalence of violence at the workplace was 14%. After adjustment, working below skill level was related statistically significantly to distress (OR 2.80) [81].…”
Section: Trauma Violence and Suicidal Ideationmentioning
confidence: 99%
“…The 12-months prevalence of violence at the workplace was 14%. After adjustment, working below skill level was related statistically significantly to distress (OR 2.80) [81].…”
Section: Trauma Violence and Suicidal Ideationmentioning
confidence: 99%
“…The prevalence of moderate to high perceived stress was 67.96% (95%CI: 65.33-70.59) and symptoms of depression was 69.69% (95%CI: 67.10-72.29). A comparable study in Europe 21 reported 63% of low-skilled workers to exhibit symptoms of distress. Moreover, stress and depression are often cited as the most predominant factors associated with reduced QOL scores, with some studies finding depression to be the most influential on QOL, and vice-versa 22 .…”
Section: Demographic Characteristicsmentioning
confidence: 83%
“…Also, a study in Germany reported a 14% prevalence of MDS and a 29% prevalence of any depressive disorder associated with acculturation level among Turkish migrants [29]. Furthermore, according to Latin American migrants, a high prevalence of distress was shown in Germany (45%) [30] and in the United States (34%) [31]. O’Connor et al described stressors which might influence poor psychosocial well-being among Latin American migrants such as current jobs, levels of education, working conditions, time of residence in the host country, acculturation level, social and family support, among others [32].…”
Section: Discussionmentioning
confidence: 99%